Thromboelastography-Based Transfusion Algorithm Reduces Blood Product Use after Elective CABG: A Prospective Randomized Study - İSBİR, CEMİL SELİM; AK, KORAY; ARSAN, SİNAN; TETİK, ŞERMİN (WILEY, 2009)
P>Objective: Bleeding and allogeneic transfusion remain constant problems in cardiac surgical procedures. In this study, we aimed to test the role of a routine thromboelastography (TEG)-based algorithm on bleeding and transfusions in patients undergoing elective coronary artery bypass grafting (CABG). Methods: Patients (n = 224) undergoing elective CABG with cardiopulmonary bypass were prospectively randomized into two groups according to transfusion strategy: in group 1 (clinician-directed transfusion, n = 110) need for blood transfusion was based on clinician's discretion and standard coagulation tests and in group 2 (TEG algorithm group, n = 114) kaolin-activated (k) TEG-based algorithm-guided perioperative transfusion management. Transfusion, blood loss, and outcome data were recorded. Results: There were no differences in consumption of packed cell units, blood loss, re-exploration for bleeding, and early clinical outcome between the groups. Patients in the TEG group had significantly lower median units of fresh frozen plasma and platelets compared with the other group (p = 0.001). The median number of total allogeneic units transfused (packed cells and blood products) was significantly reduced in the TEG group compared with the other group (median 2, range 1-3 units vs. median 3, range 2-4 units, respectively, p = 0.001). The need for tranexamic acid was significantly diminished in the TEG group compared with the other group (10.3% vs. 19%, respectively, p = 0.007). Conclusion: Our results show that routine use of a kTEG-guided algorithm reduces the consumption of blood products in patients undergoing elective CABG. Adopting such an algorithm into routine management of these patients may help to improve clinical outcome and reduce the potential risks of transfusion-related complications and total costs after CABG. (J Card Surg 2009;24:404-410).
Keywords: CARDIAC-SURGERY; CARDIOPULMONARY BYPASS; TRANEXAMIC ACID; OPERATIONS; THROMBELASTOGRAPHY; CONSERVATION